Irisin is an Effector Molecule in Exercise Rehabilitation Following Myocardial Infarction (Review) - Qin, Shuguang; Tian, Zhenjun; Boidin, Maxime; Buckley, Benjamin J. R.; Thijssen, Dick H. J.; Lip, Gregory Y. H. (Frontiers in Physiology, 2022)
Background Regular exercise is an effective non-pharmacological therapy for treatment and prevention of cardiovascular diseases (CVD). The therapeutic benefits of exercise are mediated partly through improved vascular and increase in metabolic health. Release of exercise-responsive myokines, including irisin, is associated with beneficial effects of exercise in CVD patients. Observations The present review provides an overview of the role of exercise in cardiac rehabilitation of patients with myocardial infarction (MI). Further, the role of irisin as a motion-responsive molecule in improving vascular and metabolic health is explored. Possible mechanism of cardioprotective effect of irisin-mediated exercise on myocardial infarction are also summarized in this review. Conclusions and significance of the review Irisin is associated with reduced inflammation, antioxidant properties, and anti-apoptosis effect, implying that it is a potential key mediator of the beneficial effects of exercise on vascular and metabolic health. The findings show that irisin is a promising therapeutic target for treatment of cardiovascular patients, particularly post-MI. Further research should be conducted to elucidate the potential mechanisms of cardioprotective effects of irisin and explored whether irisin induced by exercise exerts rehabilitation effects post-MI.